2022
DOI: 10.1259/bjr.20220149
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of human papilloma virus associated oropharyngeal squamous cell carcinoma and its impact on diagnosis, prognostication, and response assessment

Abstract: The clinical behaviour and outcomes of patients with oropharyngeal cancer (OPC) may be dichotomised according to their association with human papilloma virus (HPV) infection. Patients with HPV-associated disease (HPV +OPC) have a distinct demographic profile, clinical phenotype and demonstrate considerably better responses to chemo-radiotherapy. This has led to a reappraisal of staging and treatment strategies for HPV +OPC, which are underpinned by radiological data. Structural modalities, such as computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…When it comes to HPV-correlation, multiple studies have shown that HPV + cancers tend to present themselves with higher SUVmax values when compared to HPV- tumors [ 41 , 45 ]. As such PET-CT can be another instrument to help infer HPV status in oropharyngeal cancer.…”
Section: Diagnostic Role Of Pet-ctmentioning
confidence: 99%
“…When it comes to HPV-correlation, multiple studies have shown that HPV + cancers tend to present themselves with higher SUVmax values when compared to HPV- tumors [ 41 , 45 ]. As such PET-CT can be another instrument to help infer HPV status in oropharyngeal cancer.…”
Section: Diagnostic Role Of Pet-ctmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) is the reference imaging technique for the evaluation of SCC due to its better soft tissue visualization than Computed Tomography (CT) [ 8 , 9 ]. For this reason, MRI is also recommended for staging by the American Joint Committee on Cancer [ 2 , 10 12 ]. Chemoradiotherapy (RT-CHT) is one of the cornerstones for treatment of both early and locally advanced forms of NPC, although outcome is very heterogeneous [ 6 , 13 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there are reports on diverging imaging features of both primary tumor site and affected lymph nodes depictable on computed tomography (CT) and magnetic resonance imaging (MRI), differentiation of HPV infection status by cross-sectional imaging on an individual basis is still considered challenging [8]. The radiomics research field leverages reproducible quantitative representations of gray value patterns to convert medical imaging data into minable high-dimensional feature space to facilitate machine-based analysis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%